Implications of Power and Stakeholder Interest in the Implementation of Child Friendly City (CFC) Policies in Yogyakarta City - Sofiyah (GoAcademica Research & Publishing, 2022)
The Child-Friendly City (CFC) is one of the policies developed by Yogyakarta City government to fulfill children’s rights by involving the role of stakeholders. Its implementation, however, has not optimally involve stakeholders, especially in conducting socialization and supporting the facilities to fulfill of children's rights. As the main implementers of the regional development, they must play an active role in accelerating the CFC. Thus, stakeholder mapping in the implementation of CFC policies is important to be analyzed in order to figure out the stakeholders’ interests as the basis for uniting all efforts in realizing Yogyakarta City’s Grand Design as a child-friendly city. A qualitative method with a case study research strategy was employed to analyze the stakeholders’ implementation of this policy. The result of the stakeholder mapping showed that as the key player, the Regional Development Planning Agency (Bappeda) needs to strengthen the role of coordination in synergy and integration to develop stakeholders’ potential and interests in the context setter, subject and crowd categories. Furthermore, the Yogyakarta City Government needs to carry out stakeholder engagement from the technical aspect to expand support in achieving the CFC target. Therefore, strengthening collaboration and stakeholder interest in CFC policies need to be implemented as a strategic step for the government in accelerating the CFC development according to the target set as the common goal.